Phage Therapy is Effective in Protecting Honeybee Larvae from American Foulbrood Disease. Issue 1 (1st July 2015) - Ghorbani-Nezami, Sara; LeBlanc, Lucy; Yost, Diane G.; Amy, Penny S.
Abstract : American foulbrood disease has a major impact on honeybees ( Apis melifera ) worldwide. It is caused by a Gram-positive, spore-forming bacterium, Paenibacillus larvae . The disease can only affect larval honeybees, and the bacterial endospores are the infective unit of the disease. Antibiotics are not sufficient to combat the disease due to increasing resistance among P. larvae strains. Because of the durability and virulence of P. larvae endospores, infections spread rapidly, and beekeepers are often forced to burn beehives and equipment. To date, very little information is available on the use of bacteriophage therapy in rescuing and preventing American foulbrood disease, therefore the goal of this study was to test the efficacy of phage therapy against P. larvae infection. Out of 32 previously isolated P. larvae phages, three designated F, WA, and XIII were tested on artificially reared honeybee larvae infected with P. larvae strain NRRL B-3650 spores. The presence of P. larvae DNA in dead larvae was confirmed by 16S rRNA gene-specific polymerase chain reaction amplification. Survival rates for phage-treated larvae were approximately the same as for larvae never infected with spores (84%), i.e., the phages had no deleterious effect on the larvae. Additionally, prophylactic treatment of larvae with phages before spore infection was more effective than administering phages after infection, although survival in both cases was higher than spores alone (45%). Further testing to determine the optimal combination and concentration of phages, and testing in actual hive conditions are needed.